The Diagnostic Support Tool - Quality Function Deployment and its Implementation Possibilites to Urban Public Transport Quality Management - Andriskova, Ivana; Strenitzerova, Mariana (Communications - Scientific letters of the University of Zilina, 2014)
This paper deals with the diagnostic support and its implementation possibilities to urban public transport quality management in the city of Zilina. It describes the Quality Function Deployment method with its own House of Quality tool along with its building. The complex building of the House of Quality was made in order to identify the key drivers needed to be improved for higher customers’ satisfaction with the service quality.